Elite strategy in resilient authoritarianism: Equatorial Guinea, 1979–2023 - Matthews, A. S.; Sá, A. L. (Democratization, 2024)
The Equatoguinean dictatorship under Teodoro Obiang Nguema has spanned forty-four years, making him the longest-serving current head of state. Since his entry to power through a 1979 coup, Obiang has evolved in his style of governance. First ruling through a military junta, then a single-party regime, and finally competitive authoritarianism. Across these eras, he has relied on a cadre of supporting elites to occupy top spots in the state administration. Has his strategy of retaining and dismissing these top elites evolved with his broader style of governance? What features has he looked for over time to signal loyalty? We explore these questions using original individual-level data on all ruling elites in Equatorial Guinea from 1979 to 2023. Drawing on a suite of biographical variables, we find evidence that certain professional and personal traits have made elites less likely to be dismissed at different eras of Obiang’s rule. However, co-regionality has been an enduring preference in his elite strategy, suggesting his preference for friends from “back home.” These findings demonstrate how elite strategies of dictators move beyond the ethnocentric and evolve alongside broader regime characteristics.